PENGARUH PENGALAMAN DOSEN DAN FASILITAS KULIAH TERHADAP MINAT BELAJAR MAHASISWA DI UNIVERSITAS MAHKOTA TRICOM UNGGUL - Syahfendy, Harman; Novirsari, Emma; Theodora, Eka Martyna (MTU PRESS, 2025)
This study aims to determine the effect of Lecturer Experience and Lecture Facilities on Student Learning Interest at Mahkota Tricom Unggul University. This study uses a quantitative method with a survey method involving 335 people as respondents from the population and a sample of 77 people using the Slovin formula. The results of the study indicate that lecturer experience has a positive and significant effect on student learning interest, seen from the lecturer experience figure (0.000) which is smaller than the alpha 5% (0.05) or t count 3.879 > t table 1.992. The results of the study of the lecture facility variable have a positive and significant effect on student learning interest, reviewed from the figures, namely the lecture facility variable (0.000) which is smaller than the alpha 5% (0.05) or t count 4.088 > t table 1.992. From the results of the coefficient of determination, it is explained that the learning interest of Mahkota Tricom Unggul University students is caused by lecture facilities and lecturer experience by 39.7%, the remaining 60.3% is influenced by other variables not examined in this study.